Odpowiedzi

2010-01-06T18:43:02+01:00
A) 3s+5t=-6
1,5s-2t=-3t

3s+5t=-6
1,5s-2t=-3t /*(-2)

3s+5t=-6
-3s+4t=-6t

15t=6 /:15
t= 0,4

3s+5*0,6=-6
t= 0,4

3s=-3 /:3
s=1
t=0,4

b)5=3x-y
5x-2y=7

-3x=-y-5
5x-2y=7

-3x=-y-5 /*2
5x-2y=7

-6x=-2y-10
5x-2y=7

-x=-2y-10 /:(-1)
5x-2y=7

x=2y+10
5(2y+10)-2y=7

x=2y+10
10y+50-2y=7

x=2y+10
8y=-43 /:8

x=2y+10
y=5,375

x=2*5,375+10
y=5,375

x=10,75+10
y=5,375

x=20,75
y=5,375

c)x-3y=5
y+3x=-5

x-3y=5 /*(-3)
y+3x=-5

-3x+9y=-15
y+3x=-5

10y=-20 /:10
y=-2
x-3y=5
y=-2
x-6=5
y=-2
x=11
2010-01-06T18:43:33+01:00
A] 3s+5t=-6 3s+5t=-6
1,5s-2t=-3t |*(-2) -3s+4t=6t

3s+5t-3s+4t-6t=-6 <--3s i -3s skreśl ; )
3t=-6 |:3
t=-2

3s+5*(-2)=-6 3s=-6+10 3s=4 |:3 s=3/4
t=-2 t=-2 t=-2 t=-2

b]5=3x-y |*(-2) -6x+2y=-10
5x-2y=7 5x-2y=7

-6x+2y+5x-2y=-10+7 <--2y i -2y skreśl
-8y=-3 |:(-8)
y=0,375

5x-2*0,375=7 5x=7+0,75 5x=7,75 |:5 x=1,55
y=0,375 y=0,375 y=0,375 y=0,375

c]x-3y=5 x-3y=5
y+3x=-5 |*3 3y+9x=-15

x-3y+3y+9x=5-15 <---3y i 3y skreśl
10x=-10 |:10
x=-1

-1-3y=5 -3y=5+1 -3y=6 |:(-3) y=-2
x=-1 x=-1 x=-1 x=-1